Evaluation of Solid Waste Management Techincal Aspect In Taman Sari District, West Jakarta - Pramiati Purwaningrum (Journal of Environmental Engineering and Waste Management, 2023)
The solid management system in Taman Sari district, West Jakarta still uses collect-transport-dispose system. The population of Taman Sari District is 130,110 people with a total waste generation of 399,96 m3/day. This study aims to evaluate the operational technical aspects of the waste management system in Taman Sari district, which includes solid containerization, collection, and transportation of waste to final disposal at TPST Bantargebang. This research was conducted using primary data collection methods and secondary data obtained by conducting interviews, questionnaires, and field observations. The sampling method used is the Stratified Random Sample technique using the variable income level of the community at the sampling location, low income, middle income, and high income. The Taman Sari district sampling location selected 3 (three) locations namely Pinangsia Village, Krukut Village, and Keagungan Village which resulted in 45 samples for domestic waste and 26 samples for non-domestic waste. The observation results show that the aspect of waste disposal in low-income settlements is inadequate, while the aspect of disposal in middle-income and high-income settlements and commercial areas already has adequate disposal. The solid collection aspect of Taman Sari district consists of direct individual, indirect individual, and direct communal patterns. However, the solid transportation pattern in low – high income settlements only has 1-2 rounds which results in TPS overload. Therefore, the solid management system implemented in Taman Sari district needs to be evaluated to determine suitable alternatives for improving the existing conditions of the operational technical aspects of waste management in Taman Sari district.